Interpreting Asceticism with Islamic Moderation in Life: A Comparative Study of Mafatih Al-Ghaib and Al-Munir from the Story of Qarun - Moh. Ali Ghafir; Sujiat Zubaidi Saleh (al-Afkar, Journal For Islamic Studies, 2024)
The initial meaning of asceticism seems to avoid worldly life and only focuses on ukhrawi things. In this modern era, this kind of meaning will cause setbacks in all aspects of life. The meaning of asceticism needs to be further developed and adapted to modern life without abandoning principles such as ukhrawi affairs. In this research, we will examine the identification of the meaning of classical asceticism and young asceticism from the advice verses for Qarun in QS: Al-Qashah:76-77 by comparing two books of classical and contemporary tafsir, classical tafsir using the book Mafatih al-Ghaib and contemporary books using the book Al-Munir. In the message to Qarun there is still a dilemma for him, whether Qarun should change his attitude by abandoning his accumulated wealth and stopping in his worldly endeavors and only focusing on obedience to worship. Or be moderate by continuing to run your business well, but the wealth is enjoyed as best as possible according to your needs and used in a way that is approved by Allah. The research method used is literature. The basis of analysis used by researchers is the content analysis method.  With reference to these two main references, and other supporting references, the author concludes that he finds the meaning of classical asceticism and modern asceticism from the books Mafatih al-Ghaib and Al-Munir. The meaning of classical asceticism is found in the interpretation of Ar-Rosi in the advice to the third Qarun and the meaning of modern asceticism is found in the advice to the third Qarun as well. Ar-Rozi emphasized focusing on Ukrainian affairs in interpreting the advice for this third Qarun. In the third interpretation, Wahbah Az-Zuhaili equates or balances worldly and spiritual affairs or with the concept of wasthiyah al-Islam fi al-hayat or Islamic moderation in life. In the book Al Munir asceticism is interpreted as Islamic muderation in life or wasthiyah al-Islam fi al-hayat. This means that asceticism does not only focus on the ukhrawi and leaves the world.